Concentrations and loadings of organophosphate and replacement brominated flame retardants in house dust from the home study during the PBDE phase-out. (January 2020) - Percy, Zana; La Guardia, Mark J.; Xu, Yingying; Hale, Robert C.; Dietrich, Kim N.; Lanphear, Bruce P.; Yolton, Kimberly; Vuong, Ann M.; Cecil, Kim M.; Braun, Joseph M.; Xie, Changchun; Chen, Aimin
Abstract: Polybrominated diphenyl ethers, a class of flame retardants and endocrine disruptors, have been substituted in new products by organophosphate (OPFR) and replacement brominated flame retardants (RBFR). OPFRs and RBFRs readily migrate from consumer products into dust where humans are exposed via incidental ingestion and inhalation. We quantified concentrations and loadings of OPFRs and RBFRs in house dust samples (n = 317) collected from the homes of Cincinnati women between 2003 and 2006 and examined their associations with demographic and house characteristics. Tris-(1-chloro-2-propyl)-phosphate (TCIPP, geometric mean [GM]: 2140 ng g −1, range: 70.1–166, 000 ng g −1 ), tris-(1, 3-dichloro-2-propyl)-phosphate (TDCIPP, GM: 1840 ng g −1, range: 55.2–228, 000 ng g −1 ), triphenyl phosphate (TPHP, GM: 1070 ng g −1, range: 34.1–62, 100 ng g −1 ), 2-ethylhexyl-2, 3, 4, 5-tetrabromobenzoate (EH-TBB, GM: 59.5 ng g −1, range: 2.82–7800 ng g −1 ), and bis-(2-ethylhexyl)-tetrabromophthalate (BEH-TEBP, GM: 121 ng g −1, range 2.17–13, 600 ng g −1 ) were all detected in >90% of dust samples; tris-(2-chloroethyl)-phosphate (TCEP, GM: 669 ng g −1, range: 56.8–160, 000 ng g −1 ) was detected in 80.1% of samples. Concentrations of EH-TBB and BEH-TEBP increased in house dust from 2003 to 2006. The number of people living in the home, race, education, floor type, and year of sample collection were associated with some OPFR and RBFR concentrations and loadings. This study suggests that OPFRs and RBFRs were ubiquitous in house dust during the PBDE phase-out and justifies more research on the consequences of exposure to these environmental chemicals. Graphical abstract: Image 1 Highlights: We measured OPFRs and RBFRs in 317 women's house dust during the PBDE phase-out. OPFR concentrations were about 10× higher than RBFR concentrations. RBFR concentrations increased from 2003 to 2006. Both sociodemographic and housing characteristics were related to dust levels.